Integrated accounting for windows - Klooster, Dale A.; Allen, Warren ;Owen, Glenn (Taguig City, Philippines : Cengage Learning Asia Pte Ltd, 2015)
Packed with practical applications and step-by-step instructions, INTEGRATED ACCOUNTING + GL CD, 8e thoroughly illustrates computerized accounting and operating procedures for Windows-based programs. The new edition takes full advantage of the Windows environment. Preparing you for real-world practice, the general ledger software emulates commercial software packages. Detailed instruction and clear examples fully explain the software while all-new problem data sets give you plenty of hands-on experience. INTEGRATED ACCOUNTING gradually introduces software through opening balance files, showing you how to process ongoing accounting systems. As a result, you learn accounting topics while gaining software experience. Each chapter offers a sample problem, a student exercise, two software problems (with audit questions), and the use of a student-solution checker--enabling you to work at you own pace.
1. Introduction -- 2. Accounting cycle of a services business and bank reconciliation -- 3. Accounts Payable: Purchase order processing and inventory control -- 4. Accounts Receivable: Sales Order processing and inventory control -- 5. Accounting cycle of a merchandising business and budgeting -- 6. Fixed Assets -- 7. Payroll -- 8. Partnerships and corporations -- 9. Financial statement analysis -- 10. Departmentalized Accounting -- 11. Accounting system Setup -- Appendix A: Accounting cycle of a merchandising business: Using special journals.-- Index
Previously published: Integrated accounting for Windows / Dale H. Klooster, Warren W. Allen. Australia ; Mason, OH : South-Western Cengage Learning, c2011.
Includes index.
Keywords: ACCOUNTING -- DATA PROCESSING -- SOFTWARE